2013
DOI: 10.1155/2013/406049
|View full text |Cite
|
Sign up to set email alerts
|

SAR and Computer-Aided Drug Design Approaches in the Discovery of Peroxisome Proliferator-Activated Receptor γ Activators: A Perspective

Abstract: Activators of PPARγ, Troglitazone (TGZ), Rosiglitazone (RGZ), and Pioglitazone (PGZ) were introduced for treatment of Type 2 diabetes, but TGZ and RGZ have been withdrawn from the market along with other promising leads due cardiovascular side effects and hepatotoxicity. However, the continuously improving understanding of the structure/function of PPARγand its interactions with potential ligands maintain the importance of PPARγas an antidiabetic target. Extensive structure activity relationship (SAR) studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 188 publications
0
9
0
Order By: Relevance
“…This further supports our hypothesis that ligand 9l could also be expected to have increased transcriptional activity compared to 9k. It is well known that the conformation of the so called charge-clamp pair [ 10 , 22 ], which consists of the residues Lys301 and Glu471, is critical for the coactivator binding [ 23 , 24 ], in parallel with the important role of Tyr473 for the PPARγ agonistic features [ 5 ]. Thus, our data reveal the main reason of the observed antagonism of the compound 9p: it can be related to the disruption of the binding pockets of both the natural ligand and the coactivator, due to the described above structural perturbation induced by its interactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This further supports our hypothesis that ligand 9l could also be expected to have increased transcriptional activity compared to 9k. It is well known that the conformation of the so called charge-clamp pair [ 10 , 22 ], which consists of the residues Lys301 and Glu471, is critical for the coactivator binding [ 23 , 24 ], in parallel with the important role of Tyr473 for the PPARγ agonistic features [ 5 ]. Thus, our data reveal the main reason of the observed antagonism of the compound 9p: it can be related to the disruption of the binding pockets of both the natural ligand and the coactivator, due to the described above structural perturbation induced by its interactions.…”
Section: Resultsmentioning
confidence: 99%
“…A lot of data are available about the dynamics of peroxisome proliferator-activated receptor γ (PPARγ) and its agonists, collected by several experimental techniques such as hydrogen deuterium exchange (HDX) mass spectrometry, NMR and fluorescence anisotropy [ 1 , 2 , 3 , 4 , 5 ]. A detailed binding mode of this class of compounds has also been revealed by many X-ray structures deposed in the Protein Data Bank (PDB) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In silico drug design approaches are commonly used for the target identification, validation, molecular design, and drug interactions with target proteins 29 . A number of computer-aided drug discovery studies have been also conducted to find new insulin sensitizing molecules targeting PPARγ with reduced toxicity and side effects 30 . In silico studies have been reported using the structure of PPARγ LBD in complex with rosiglitazone, a representative anti-diabetic drug for PPARγ 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…A promising approach for both studying and treating metabolic syndrome involves the use of a class of drugs called thiazolidinediones [1417], previously used to treat diabetes. Rosiglitazone (RGZ), the prototypical drug in this class, activates the nuclear peroxisome proliferator-activated receptor γ (PPARγ), a type II nuclear receptor, which in turn alters the expression of numerous genes [18], ultimately resulting in reduced blood concentrations of glucose, fatty acids, and insulin [19].…”
Section: Introductionmentioning
confidence: 99%